The Life Cycle of the Corpus Luteum - Meidan, Rina.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes the life cycle of a unique endocrine gland that is absolutely essential for the establishment and maintenance of pregnancy in all mammalian species. The corpus luteum is unique because it is formed and destroyed every (non-fertile) reproductive cycle. When fertilization occurs, the corpus luteum is rescued or maintained. The processes that control corpus luteum formation, demise (luteolysis), or maintenance are just beginning to be unraveled in recent years; they involve diverse cell types and mechanisms. Some of these processes resemble tumor development$1 (Bangiogenesis, for instance$1 (Bbut interestingly enough, this resemblance is only up to a point. The corpus luteum uses mechanisms that allow its normal, physiological growth and disappearance. Pulling together key research on the corpus luteum, this volume is of interest to both reproductive endocrinologists and comparative physiologists, with clinical relevance spanning comparative animal studies to women's health.s
Luteal Angiogenesis -- Roles of Hypoxia in Corpus Luteum Formation -- Luteal Steroidogenesis -- Lipid Droplets and Metabolic Pathways Regulate Steroidogenesis in the Corpus Luteum -- Steroid Hormone Receptors in the Corpus Luteum -- Immune Cells and their Effects on the Bovine Corpus Luteum -- The Rodent Corpus Luteum -- Regulation of corpus luteum function in the domestic dog (Canis familiaris) and comparative aspects of luteal function in the domestic cat (Felis catus) -- Luteolysis in Ruminants: Past Concepts, New Insights, and Persisting Challenges -- Corpus Luteum Rescue in Nonhuman Primates and Women -- Corpus Luteum and Early Pregnancy in Ruminants -- Corpus Luteum Regression and Early Pregnancy Maintenance in Pigs -- The Corpus Luteum and Women$1 (Bs Health.s
Keywords: Medicine; Endocrinology; Reproductive medicine; Animal physiology; Medicine & Public Health; Reproductive medicine; Endocrinology; Animal physiology